Application of a biomimetic wellbore stabilizer with strong adhesion performance for hydrate reservoir exploitation. (1st April 2023) - Wang, Xingxing; Jiang, Guancheng; Wang, Guoshuai; Yang, Lili; He, Yinbo; Dong, Tengfei; Chang, Xiangyang; Chen, Haozhe
Graphical abstract: Highlights: A biomimetic wellbore stabilizer TA-PVA was developed in WBDFs for NGH reservoir. The strong adsorption mechanism of TA-PVA is based on hydrogen bond. TA-PVA can bond clay mineral particles and hydrate particles simultaneously. TA-PVA has no endothermic and exotherm phenomenon at 0–60 ℃. Abstract: Natural gas hydrate (NGH) in marine is usually reserved in the pores or cracks of weakly cemented argillaceous siltstones. Moreover, the hydrates are susceptible to variations in temperature and pressure conditions when water-based drilling fluids (WBDFs) are drilled into hydrate reservoirs, leading to the hydrate in-situ decomposition and severe sand production. In this work, an inexpensive and facilely prepared biomimetic wellbore stabilizer with strong adsorption of multiple hydrogen bonds was prepared by fusing catechol-rich tannic acid (TA) and polyvinyl alcohol (PVA) with polyol hydroxyl adsorption function, referred to as TA-PVA complex (TA-PVA). TA-PVA was added to WBDFs to strengthen the NGH reservoir wellbore for ensuring the safety of drilling process in a wide temperature range (2-60℃). The microscopic characterization of TA-PVA and its cohesion mechanism with argillaceous siltstone was investigated by Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), scanning electron microscopy (SEM) and atomic force microscopy (AFM). The mechanical properties of skeleton of the artificial hydrate cores were evaluated by compressive strength test, with maximum compressive strength reaching 0.45 MPa. And the adhesion force of TA-PVA to the probe modified by silica microsphere (PSM) was further studied by AFM. Meanwhile, the adhesion forces between TA-PVA and cyclopentane hydrate particles were measured at 1.5℃. Adhesion test results demonstrate that TA-PVA can bond clay particles, quartz sand and hydrate particles together. In detail, the adhesion force between TA-PVA and PSM reaches more than 164.46 mN/m, the adhesion force between TA-PVA droplet and cyclopentane hydrate particle reaches 43.19 mN/m. The differential scanning calorimetry (DSC)curves demonstrate that TA-PVA releases no heat between 0 and 60 °C, indicating that TA-PVA has no impact on the decomposition of NGH, showing the potential to maintain the integrity of NGH reservoir.